Detection of macrolide and fluoroquinolone resistance-associated 23S rRNA and parC mutations in Mycoplasma genitalium by nested real-time PCR - He, Wenyin; Yuan, Ying; Liang, Junyu; Fan, Xuejiao; Li, Lei; Pan, Xingfei (Frontiers in Cellular and Infection Microbiology, 2023)
Background Traditional drug susceptibility testing cannot be performed in clinical laboratories due to the slow-growing characteristics of Mycoplasma genitalium when cultured in vitro. Sanger sequencing is the standard method for detecting drug resistance-associated mutations. It has been used in some laboratories to guide the choice of macrolide antibiotics for Mycoplasma genitalium infected patients. Furthermore, resistance to fluoroquinolone has become another emerging clinical challenge. Objective Sequencing analysis can detect unknown mutations, but it is time-consuming, requires professional analytical skills and the appropriate testing equipment. The main objective of this study was to establish a nested real-time PCR method for the simultaneous detection of 23S rRNA and parC genotypes in relation to the macrolide and fluoroquinolone resistance. Results 105 MG-positive samples and 27 samples containing other pathogens were used for validation. The limit of the nested real-time PCR detection was 500 copies/reaction and there was no cross-reaction with Ureaplasma urealyticum, Mycoplasma hominis, Chlamydia trachomatis, Neisseria gonorrhoeae, Human papillomavirus, Herpes simplex virus, Candida albicans and Ureaplasma parvum, but the 23S rRNA assay cross-reacted with Mycoplasma pneumoniae. Compared with sequencing results, the sensitivity of 23S rRNA was 100% (95% CI; 93.3 -100), the specificity was 94.3% (95% CI; 79.4 - 99.0), the overall consistency was 98% (95% CI; 92.5 - 99.7) and kappa value was 0.96 (P < 0.001); the sensitivity of parC was 100% (95% CI; 93.4 - 100), the specificity was 89.7% (95% CI; 71.5 - 97.3) and the overall consistency was 96.9% (95% CI; 90.7 - 99.2) with a kappa value of 0.92 (P < 0.001). Conclusions The results of this sensitive and rapid alternative for identifying resistant genotypes of Mycoplasma genitalium are intuitive and easy to interpret, especially for mixed MG populations. Although the relevant 23S rRNA primers need further adjustment, this reliable method would provide an effective diagnostic tool for the selection of antibiotics in clinical practice.